2022
DOI: 10.1155/2022/4918294
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation of Clinicopathological Factors with Brain Tumor-Related Epilepsy in Glioma

Abstract: Objectives. Glioma patients with brain tumor-related epilepsy (BTRE) have a complex profile due to the simultaneous presence of two pathologies, glioma and epilepsy; however, they have not traditionally received as much attention as those with more malignant brain tumors. The underlying pathophysiology of brain tumor-related epilepsy remains poorly understood. The purpose of this study was to investigate the possible correlation between molecular neuropathology and glioma with BTRE and a wide range of BTRE-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Wang et al. conducted a retrospective cohort study of 186 glioma patients; 100 based on the results of the immunochemical assay, the authors showed that glioma patients with a positive variant of the ATRX gene in the non‐epilepsy group were less likely to develop epilepsy than those in the epilepsy group. You et al.…”
Section: Omics Studies On the Occurrence Development And Mechanisms O...mentioning
confidence: 99%
“…Wang et al. conducted a retrospective cohort study of 186 glioma patients; 100 based on the results of the immunochemical assay, the authors showed that glioma patients with a positive variant of the ATRX gene in the non‐epilepsy group were less likely to develop epilepsy than those in the epilepsy group. You et al.…”
Section: Omics Studies On the Occurrence Development And Mechanisms O...mentioning
confidence: 99%
“…A series of compounds structurally related to flavonoid icariin has been obtained through the reaction of the 3‐hydroxy group of the aglycone form of icariin with various sulfonyl chlorides. [ 293 ] Of the four thiophene‐containing sulfonates 322 (Figure 37) in this collection, compound 322 (R = COOCH 3 ) was devoid of antibacterial activity, while compounds 322 (R = H or Br) had moderate antibacterial activity. Thiophene 322 (R = Cl) exhibited an overall good activity, as it was equipotent to ciprofloxacin against two MRSA strains and possessed half of the activity of ciprofloxacin against the other two MRSA strains and one methicillin‐sensitive S. aureus strain.…”
Section: Antimicrobial Activity Of Miscellaneous Thiophenesmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%